2020
DOI: 10.1155/2020/6173217
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge regarding Alzheimer’s Disease among College Students of Kathmandu, Nepal

Abstract: Introduction. Alzheimer’s, a neurodegenerative disease, is becoming a growing burden and the leading cause of disability among older people, and there is no cure for it. It is set to be the biggest killer among the growing elderly population. The aim of this study was to assess the knowledge of Alzheimer’s disease among college students in Kathmandu metropolitan city. Methods. This was a descriptive cross-sectional study among 385 randomly selected bachelor students of Kathmandu metropolitan city. The question… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
14
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 16 publications
1
14
0
1
Order By: Relevance
“…The highest prevalence of adolescent suicide is evidenced in Southeast Asia and Eastern Europe [ 3 ]. It can be persistent, comprehensively impairing adolescent's ability to function at work or school and to cope with daily life [ 5 , 6 ]. Literatures have revealed that sleeping disorder may cause psychiatric disorders and psychological stress leading to acute and chronic depression [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The highest prevalence of adolescent suicide is evidenced in Southeast Asia and Eastern Europe [ 3 ]. It can be persistent, comprehensively impairing adolescent's ability to function at work or school and to cope with daily life [ 5 , 6 ]. Literatures have revealed that sleeping disorder may cause psychiatric disorders and psychological stress leading to acute and chronic depression [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Evidence on the burden of depression among adolescents in Nepal is not well measured due to the lack of adequate research [ 5 , 6 ]. In Nepal, mental health services receive insignificant attention at all levels of society, from the government to the general public.…”
Section: Introductionmentioning
confidence: 99%
“…The combined result has a relatively high mean score (mean 21.78; 95% CI 20.67–22.90) that differs significantly among subgroups ( Q test = 11.35 on 4 df; p value = 0.02), with health professionals presenting the highest mean score (11 data points, mean ADKS = 22.9), followed closely by caregivers (3 data points, mean ADKS = 21.6). A study conducted by Baral et al found that students obtained the lowest scores (ADKS score = 15.4), whereas the subgroup of health professionals yielded the highest scores in a study by Carpenter et al (ADKS score = 27.4) [ 10 , 18 ].…”
Section: Resultsmentioning
confidence: 99%
“…A study conducted by Baral et al found that students obtained the lowest scores (ADKS score = 15.4), whereas the subgroup of health professionals yielded the highest scores in a study by Carpenter et al (ADKS score = 27.4) [ 10 , 18 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation